Hypothermia as an adjuvant treatment in paediatric refractory or super‐refractory status epilepticus. (15th May 2020) - Legriel, Stephane
Abstract : Therapeutic hypothermia is among the adjuvant therapies suggested for refractory or super‐refractory status epilepticus (R/SR‐SE) in paediatric patients. Experimental evidence of neuroprotective and antiseizure effects provides a strong rationale for using therapeutic hypothermia in patients with status epilepticus. Thus, hypothermia between 20°C and 33°C in animals with status epilepticus is associated not only with significantly less neuronal damage, predominantly in the hippocampal CA1, CA2, and CA3 areas, but also with increased seizure latency and decreased seizure frequency and duration. Therapeutic hypothermia has rarely been used in paediatric R/SR‐SE. In the few reported cases, seizure control was markedly improved but nearly half the patients experienced recurrences after rewarming. Studies are needed to clarify the modalities and indications of therapeutic hypothermia in paediatric patients with R/SR‐SE. What this paper adds: Hypothermia at 20°C to 33°C is neuroprotective and has antiseizure effects in experimental status epilepticus. In children, antiseizure effects are marked but recurrences after rewarming are common. What this paper adds: Hypothermia at 20°C to 33°C is neuroprotective and has antiseizure effects in experimental status epilepticus. In children, antiseizure effects are marked but recurrences after rewarming are common.